Effects of SGLT2-inhibitor on The Expression of MicroRNA-21, Transforming Growth Factor-β1, and Matrix Metalloproteinase-2 in The Process of Cardiac Fibrosis in Hyperglycemic Model Rats - Muhammad Ridwan; Herlina Dimiati; Maimun Syukri; Ronny Lesmana; Lia Meuthia Zaini (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Sodium glucose co-transporter-2 inhibitor (SGLT2-i), a new oral antidiabetic drug, has been recommended for its morbidity and mortality benefits in patients with heart failure. This study aimed to determine the effect of acute SGLT2-i therapy on the relative ratio expression of microRNA-21 (miR-21), transforming growth factor-β1 (TGF-β1), and matrix metalloproteinase-2 (MMP-2) in the process of cardiac fibrosis in the hyperglycemia Wistar rat models compared to biguanide (metformin) therapy.METHODS: We used Streptozotocin (STZ) to induce hyperglycemia in Wistar rats (n=31), randomly divided into four groups: negative control (NC, n=4), positive control (PC, n=10), hyperglycemia plus metformin (M, n=8), and hyperglycemia plus empagliflozin (E, n=9). After seven weeks, the rats were sacrificed and the heart tissue was taken for microRNA and messenger RNA (mRNA) extraction, followed by reverse transcription quantitative real time polymerase chain reaction (RT-qPCR) examination. The data was analyzed using One-way ANOVA.RESULTS: Results showed a decreasing trend in the gene expression relative ratio of miR-21 (1.0 vs. 1.9; p=0.079) and TGF-β1 (0.9 vs. 3.2; p=0.145), but a significant increase in MMP-2 gene expression (1.3 vs. 0.7; p=0.002) in the SGLT2-i (empagliflozin) vs. biguanide (metformin) groups.CONCLUSION: Empagliflozin administration may play a significant role in preventing the occurrence of cardiac fibrosis in hyperglycemia.KEYWORDS: sodium glucose co-transporter-2 inhibitor, microRNA-21, transforming growth factor-β1, matrix metalloproteinase-2, cardiac fibrosis